Temozolomide in combination with interferon-alfa versus temozolomide alone in patients with advanced metastatic melanoma: a randomized, phase III, multicenter study from the Dermatologic Cooperative Oncology Group - Kaufmann, Roland; Schadendorf, Dirk (Journal of clinical oncology, 2016)
Purpose: Temozolomide (TMZ) has shown efficacy in metastatic melanoma equal to that of dacarbazine (DTIC), the standard chemotherapeutic agent for melanoma. As the combination with interferon-alfa (IFN-α) appears superior to single-agent DTIC regarding response rates, the purpose of this study was to compare TMZ alone and TMZ plus IFN-α in terms of objective response (OR), overall survival, and safety in a prospective, randomized, multicenter trial. Patients and Methods: Two hundred ninety-four patients with untreated stage IV metastatic melanoma (American Joint Committee on Cancer staging system) were randomly assigned to receive either oral TMZ alone (200 mg/m2/day; days 1 through 5 every 28 days) or in combination with subcutaneous IFN-α (5 MU/m2; days 1, 3, and 5 every week). Results: Two hundred eighty-two patients were eligible for an intent-to-treat analysis, 271 patients were treated per protocol. In the TMZ + IFN-α arm, 33 (24.1%) of 137 patients responded to therapy (partial or complete remission) whereas in the monotherapy arm, in 18 (13.4%) of 134 patients, a response was evident. Thus, the response rate was significantly higher in the combination arm (P = .036). Median survival time was 8.4 months for patients treated with TMZ (95% CI, 7.07 to 9.27) and 9.7 months for those treated with the combination (95% CI, 8.26 to 11.18; P = .16). Dose modifications and interval prolongations due to hematologic toxicity were significantly more frequent in the TMZ + IFN-α arm (P < .001). Conclusion: In metastatic melanoma treatment with TMZ + IFN-α leads to a significantly superior OR rate compared to treatment with TMZ alone, which did not translate into prolonged survival in our study population.